One-pot synthesis of redox-triggered biodegradable hybrid nanocapsules with a disulfide-bridged silsesquioxane framework for promising drug delivery. Issue 23 (8th February 2017) - Zhou, Mengyun; Du, Xin; Li, Weike; Li, Xiaoyu; Huang, Hongwei; Liao, Qingliang; Shi, Bingyang; Zhang, Xueji; Zhang, Meiqin
Abstract : Redox-triggered biodegradable hybrid nanocapsules with the disulfide-bridged silsesquioxane framework were developed for promising drug delivery. Abstract : Biodegradability is very critical for biomaterials to be nanocarriers. Ideal nanocarriers should be stable enough to execute their functions, but then can be efficiently got rid of, by either biodegradation or excretion. In this work, we report the design and one-pot fabrication of a series of uniform organic–inorganic hybrid nanocapsules with a disulfide-bridged silsesquioxane framework and a particle size smaller than 100 nm for redox-triggered biodegradation. The optimal synthesis conditions were explored for balancing the nanostructure, sulfur (S) content and aggregation degree. Fluorescent molecules were also integrated into the disulfide-bridged silsesquioxane framework by a co-condensation strategy for fluorescence tracking. Dithiothreitol (DTT) as a strong model reducing agent triggered the breakdown of hybrid nanocapsules without and with PEG modification from intact nanospheres to small fragments, while intracellular glutathione (GSH) had a slightly lower capacity of biodegrading these nanocapsules. The constructed delivery system obviously inhibited the growth of A549 cancer cells due to efficient cellular uptake by an endocytosis pathway and the subsequent pH and GSH-triggered drug release. The possibility of regulating the framework and surface functionalization of hybrid nanocapsules opens new opportunities for the development of silica-based degradable hybrid nanocarriers for promising drug delivery.